Effects of Culture Duration, Follicle Stimulating Hormone (FSH) Type, and Activin A Concentration on In Vitro Growth of Preantral Follicles and Maturation of Intrafollicular Oocytes - Jung Kyu Choi (The Korean Society of Animal Reproduction and Biotechnology, 2019)
The objective of this study was to establish an in vitro culture system for ovarian preantral follicles of B6D2F1. First, we optimized the in vitro preantral-follicle culture by culture duration, follicle stimulating hormone (FSH) type, and activin A concentration. Duration of in vitro culture for 9, 11, and 13 days was sufficient for the normal development of preantral follicles to antral follicles. Formation of cumulus cell-oocyte complex (COC) was induced by treatment with human chorionic gonadotropin (hCG; 2.5 IU/mL) and epidermal growth factor (EGF; 5 ng/mL). In addition, metaphase II (MII) oocytes formed during this in vitro culture of preantral follicles. In vitro preantral-follicle culture for 9 days showed higher rates of growth and maturation, thus yielding a greater number of antral follicles, and there were significant differences (p < 0.05) in the number of MII oocytes (that formed from these preantral follicles via differentiation) between the 9-day culture and 11-day or 13-day culture. The follicles cultured for 9 days contained a tightly packed well-defined COC, whereas in follicles cultured for 11 days, the COC was not well defined (spreading was observed in the culture dish); the follicles cultured for 13 days disintegrated and released the oocyte. Second, we compared the growth of the preantral follicles in vitro in the presence of various FSH types. There were no significant differences in the growth and maturation rates and in differentiation into MII oocytes during in vitro culture between preantral follicles supplemented with FSH from Merck and those supplemented with FSH from Sigma. To increase the efficiency of MII oocyte formation, the preantral follicles were cultured at different activin A concentrations (0 to 200 ng/mL). The control follicles, which were not treated with activin A, showed the highest rate of differentiation into antral follicles and into MII oocytes among all the groups (0 to 200 ng/mL). Therefore, activin A (50 to 200 ng/mL) had a negative effect on oocyte maturation. Thus, in this study, we propose an in vitro system of preantral-follicle culture that can serve as a therapeutic strategy for fertility preservation of human oocytes for assisted reproductive medicine, for conservation of endangered species, and for creation of superior breeds.